Genotype x environment interaction for morpho-agronomic traits and color parameters in cassava in the Central Amazon - Costa, E.I.; Ticona-Benavente, César Augusto; Silva Filho, Danilo Fernandes da (Genetics and Molecular Research, 2022)
The Amazon harbors numerous bitter cassava genotypes, of which only a few have been studied agronomically. We evaluated the genotype x environment interaction (GxE) displayed by seven traditional varieties found in the Brazilian municipalities of Lábrea-AM, 07°14‟83.5”S, 64°44‟70”W, (Cobiçada, Minerva, and Flecha-Amarela) and Manaus-AM, 02º59‟00”S, 60º01'00”W, (Mana, Trairinha, Nanica, and Jurará), to determine the landraces best adapted to both sites. A randomized block design, with seven treatments and four replications with eight plants per plot, was adopted at each site. We evaluated commercial root number, length, diameter, length/diameter ratio, mass, dry matter, peel thickness, pulp coloring, plant height, stem diameter, and aerial part mass. GxE interaction analysis revealed GxE interaction for plant height and root diameter and number, and yield. Jurará was the most adapted variety at both sites for the main agronomical characteristics. It showed 43.7 and 26.5 t ha-1 root yield; 39.8 and 43.7 t ha-1 aerial mass; 10.8 and 4.8 roots per plant and 331.7 and 316.6 cm plant height, respectively in Lábrea and Manaus, respectively. Therefore, Lábrea and Manaus are suitable sites for making studies of GxE interaction. Jurará can be recommended for the Amazon region as well and should be tested in other tropical and subtropical regions.
Keywords: Manihot esculenta; Landraces; Manioc